Da’wah with prophetic leadership by Kh. M. Wazir Dahlan at the Darul Amal Islamic Boarding School, Bengkulu - Nafsih, Syarifatun; Syarifah, Zakiatus (Jurnal Ilmiah Syi'ar, 2023)
This study aims to describe and analyze the implementation of prophetic leadership by KH. M. Wazir Dahlan at Darul Amal Bengkulu Islamic Boarding School. This study uses a descriptive qualitative approach. The research results show that KH. M. Wazir Dahlan in his prophetic leadership at the Darul Amal Bengkulu Islamic Boarding School centered on five things, namely uswah hasanah and religious provision, shiddiq, amanah, tabligh and fathonah. Uswah hasanah and religious provision by setting an example like the Prophet to follow as well as spiritual and scientific provision as a strengthening of faith. The next prophetic implementation is shiddiq by always being honest in actions that will foster strong character by being honest divided into three by being honest with God, to yourself and to others. Trustworthiness is divided into two, namely Fulfilling Commitment and reliability. Next is tabligh (delivering) which includes being able to communicate da'wah effectively, having a clear vision, having noble visions and ideals that are shared, being an example and role model for everyone, being able to motivate and inspire, having genuine concern and touch, and The last is being able to work together. The last implementation is fathonah in leadership by having to become a learner as well as a teacher, having a strategy in achieving its goals, then deliberation and finally managing time by always being istiqamah in getting closer to Allah and improving one's performance as a leader.